Dynamics of valence-shell electrons and nuclei probed by strong-field holography and rescattering - Samuel G. Walt (Nature Portfolio, 2017)
Capturing ultrafast molecular dynamics is difficult as the process involves coupled and very fast motions of electrons and nuclei. Here the authors study non-adiabatic dynamics in the NO molecule using strong-field photoelectron holography to shed light on the valence-shell electron dynamics.